Optimizing The Synergy Of Sharia Economy, Digital Economy, and Creative Economy On The Competitiveness Of MSMEs in North Sumatra - Pulungan, Ja'far Hamzah (Applied Business and Administration Journal, 2025)
This study aims to analyze the synergy between the sharia economy, digital economy, and creative economy in enhancing the competitiveness of MSMEs in North Sumatra. Utilizing Structural Equation Modeling (SEM), we examine how each element contributes to improving market access and competitiveness. The findings indicate that the sharia and digital economies positively influence market access, while the creative economy shows a negative correlation due to various challenges in infrastructure and market understanding. This study highlights the importance of integrated policies, digital platforms, and sharia-based financing to create a more competitive and sustainable MSME sector in North Sumatra. The results emphasize the need for stakeholder collaboration to address the gaps in the creative economy and fully capitalize on the synergies of these economic systems.